Study on Liveness Detection for Fingerprint Biometrics - G. Arunalatha; M. Ezhilarasan (Research Developments in Science and Technology Vol. 10, 2022)
Biometrics is the process of automatically recognising people based on their biological and behavioural features. Biometric security systems are commonly used. They’re employed for both forensic and commercial purposes. Because of its permanence and uniqueness, fingerprint recognition is the most extensively used biometric technology for personal identification systems But biometric systems are vulnerable to certain type of attacks. Spoofing is the deception of a biometric system by an unauthorised person using a fake input that mimics one of the authorised person’s biometric inputs. Liveness detection adds an extra layer of security to biometrics. It is used to prevent forgeries. The fingerprint Liveness detection is performed by measuring the ridge quality features of fingerprint. As it does not require any external hardware, this technology is software-based and low-cost.